Correlates of premature pap test screening, under 25 years old: analysis of data from the CONSTANCES cohort study - Stéphanie Mignot; Virginie Ringa; Solène Vigoureux; Marie Zins; Henri Panjo; Pierre-Jean Saulnier; Xavier Fritel (BMC, 2021)
Abstract Background Many countries currently recommend that screening for cervical cancer begin at the age of 25 years. Premature screening (before that age) could lead to unnecessary follow-up examinations and procedures that turn out to be useless. Our objective is to ascertain if the use of particular contraceptive methods are associated with premature screening. Methods This cross-sectional study based on the CONSTANCES cohort enabled us to include 4297 women younger than 25 years. The factors associated with premature screening were modeled by logistic regression. Missing data were handled by multiple imputations. The multivariate analyses were adjusted for sex life, social and demographic characteristics, and health status. Results Nearly half (48.5%) the women younger than 25 years had already undergone premature screening. Women not using contraceptives (aOR 0.3, 95% CI 0.3-0.5) and those using nonmedicalized contraceptives (condom, spermicide, etc.) (aOR 0.5, 95% CI 0.4-0.6) had premature screening less often than women using birth control pills. Higher risks of premature screening were observed in 20-year-old women (aOR 2.7, 95% CI 2.2-3.3) and in those with more than 5 lifetime partners (aOR 2.5, 95% CI 2.0-3.1), compared respectively with women who were younger and those with 5 or fewer lifetime partners. Conclusion Young women using contraceptives that require a doctor's prescription are exposed to premature screening more often than those not using contraception and those with nonmedicalized contraceptives.